Informazione Geografica e PA: tra web 2.0 e mondi digitali - Di Prinzio, Luigi; Labini, Giovanni Sylos (GEOmedia, 2009)
Geographic Information and Governments: from web 2.0 to digital worlds In 1998 a visionary concept, coined "Digital Earth", was made popular by former US vice president Al Gore. This idea is that any citizen of the planet, linked through the Internet, should be able to access vast amounts of free information in this virtual world, however, a vast commercial marketplace of products and services was envisioned to co-exist. After 10 years much progress has been made. This article aims at shaping the current and future role of Government as a coordinator, controller and natural facilitator for the cooperative use of standards, databases, and tools among Geomatics stakeholders.